Hypoalbuminemia in COVID-19 patients: A Predictor of Poor Outcome - Mubashar Sultan Hashmi, Mudassar Ashraf, Umbreen Aslam, Muhammad Sohail Khalid, Zahra Nawaz, Muhammad Asim Rana, Muhammad Mansoor Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The coronavirus disease 2019 (COVID-19) has quickly spread to become a pandemic. Most studies demonstrate that increased liver enzymes in COVID-19 have little clinical relevance. In severe COVID-19, lower albumin levels are seen. Aim: To see how hypoalbuminemia levels affect the COVID-19 patients. Study design: Retrospective cohort study. Place and duration of study: Services Institute of Medical Sciences Lahore and Bahria International Hospital, Lahore from 10th January 2021 to 17th September 2021. Methodology: Sixty-seven confirmed cases of COVID-19 on RT-PCR were recruited. They were further divided into two groups. Group N (normal albumin levels) had thirty-six participants whereas group HA (hypoalbuminemia) contained thirty-one participants. Both males and females of all age groups, having complete medical records were included. Biochemical variables were noted from the medical record within 48 to 72 hours after admission. Twenty eight days follow up was done to note the mortality. Patients having incomplete medical records who expired within 2 days after admission were excluded. Results: A significantly higher number of deaths, lymphopenia, hypertensive, diabetics, and asthmatic participants were found in Group HA as compared to Group N. Hypoalbuminemia is mostly seen in older age and biochemical variables such as total leukocyte count and, neutrophils were elevated, whereas lower levels of lymphocytes were found in group HA. Lower lymphocytes and higher creatinine levels are the most prevalent predictors of mortality. The Pearson’s correlation of albumin with lymphocytes showed a positive correlation and inverse correlation with TLC, Neutrophil counts, CRP levels Conclusion: The group HA is associated with higher mortality and increased levels of prognostic factors of mortality.